2011
DOI: 10.1021/jp201839s
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Cu/Zn Interaction in SiO2Supported Methanol Synthesis Catalysts Unraveled by in Situ XAFS

Abstract: In situ X-ray absorption spectroscopy XAFS at the Cu and Zn K-edge has been used to unravel the Cu/Zn interaction and identify the possible active site of Cu-based methanol synthesis catalysts in the Cu/ZnO/SiO 2 ternary system. These highly dispersed silica supported catalysts, whose activity increases sharply as a function of the reduction temperature, were studied calcined, reduced at 200, 300, and 400°C, and for each reduction temperature under passivation/rereduction and methanol synthesis conditions. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 57 publications
9
45
0
Order By: Relevance
“…The HMFI-Zn 0 -5 sample exhibited characteristic absorption bands at 9663.7 and 9669.7 eV, being attributable to the 1s → 4p transitions for monomeric Zn 2+ ions exchanged in the MFI zeolite. 12,33 The XANES spectrum of Sample HMFI-Zn 0 -5 is consistent with that of Sample Zn 2+ -MFI (Fig. S1 †), supporting that the zinc metal-atoms used in the preparation process of the HMFI-Zn 0 -5 sample were quantitatively oxidized to monomeric Zn 2+ ions.…”
Section: Characterization Of a Synthesized [Zn 2 ] 2+ Species Into Hmfisupporting
confidence: 71%
“…The HMFI-Zn 0 -5 sample exhibited characteristic absorption bands at 9663.7 and 9669.7 eV, being attributable to the 1s → 4p transitions for monomeric Zn 2+ ions exchanged in the MFI zeolite. 12,33 The XANES spectrum of Sample HMFI-Zn 0 -5 is consistent with that of Sample Zn 2+ -MFI (Fig. S1 †), supporting that the zinc metal-atoms used in the preparation process of the HMFI-Zn 0 -5 sample were quantitatively oxidized to monomeric Zn 2+ ions.…”
Section: Characterization Of a Synthesized [Zn 2 ] 2+ Species Into Hmfisupporting
confidence: 71%
“…Previously, it has been reported that the Cu catalyst could be protected against oxidation and that leaching could be minimized by adding 50 wt% of Zn to the catalyst as a sacrificial reducing agent [53,82,83]. Consistent with this view, Figure 16b shows that a considerable yield increase was achieved when a CuZn-based heterogeneous catalyst was used in the fixed- 24 bed reactor.…”
Section: Figure 16supporting
confidence: 75%
“…The Fourier transforms (FT) of the EXAFS spectra of the Cu foil and Cu NWs shown in Figure 2d demonstrate a strong CuÀCu peak located at 2.52 Å. 42 While for the Cu NWs, the new peak at around 1.42 Å might be ascribed to the formation of CuÀN bonds at the Cu nanowire surface. 42,43 The presence of NÀCu bonds on the surface of Cu NWs would greatly restrain the oxidation process.…”
Section: Resultsmentioning
confidence: 99%